2021
DOI: 10.1016/j.ajoc.2021.101163
|View full text |Cite
|
Sign up to set email alerts
|

Long-term visual field changes after femtosecond laser-assisted cataract surgery in glaucoma patients, case series

Abstract: Purpose To assess the short and long-term changes in Visual Field (VF) Mean Deviation (MD), Visual Field Index (VFI), and intraocular pressure (IOP) after femtosecond laser-assisted cataract surgery (FLACS) in glaucomatous eyes. Materials and methods Interventional, prospective case series. Patients with glaucoma, who required cataract surgery were included. All patients underwent a complete ophthalmologic assessment and Visual Fields. FLACS was performed in all patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We also found that the DDC has no correlation with AL, ACD, or Km but has a negative correlation with LT, indicating that a thick preoperative LT led to a stable anterior capsulotomy size, possibly because the thicker lens had a higher capsular tension, which could decrease the elasticity of the capsulotomy; however, the correlation between the DDC and LT was weak, and when the FLACS technique was applied for some special patients, such as those whose AL was long or LT was thick, all PDCs were set to 5.0 mm with no special requirements when setting parameters, which is consistent with our research. [28][29][30][31] Therefore, we suggest that it may be unnecessary to consider the influence of ocular biometric factors when setting parameters in FLACS.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the DDC has no correlation with AL, ACD, or Km but has a negative correlation with LT, indicating that a thick preoperative LT led to a stable anterior capsulotomy size, possibly because the thicker lens had a higher capsular tension, which could decrease the elasticity of the capsulotomy; however, the correlation between the DDC and LT was weak, and when the FLACS technique was applied for some special patients, such as those whose AL was long or LT was thick, all PDCs were set to 5.0 mm with no special requirements when setting parameters, which is consistent with our research. [28][29][30][31] Therefore, we suggest that it may be unnecessary to consider the influence of ocular biometric factors when setting parameters in FLACS.…”
Section: Discussionmentioning
confidence: 99%
“…The IOP returned to baseline levels after 1 week and the decrease in IOP persisted through 3 years in glaucoma patients [ 101 ]. No significant changes in visual field mean deviation and visual field index were found from the baseline to 12 months after surgery in glaucoma patients [ 102 ].…”
Section: Clinical Applicationsmentioning
confidence: 99%